Pengaruh Kepuasan Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Bagian Perbendaharaan dan Mobilisasi Dana RSUP Dr Sardjito - Tutuk Wahyu Widodo (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT The purpose of this study is to describe (1) the effect of job satisfaction variable on employee performance, (2) the effect of work environment variable on employee performance, and (3) the influence of job satisfaction variable and work environment together to employee performance at Treasury and Fund Mobilization Division of Dr Sardjito Yogyakarta General Hospital. This study uses quantitative approach with causal associative research category, with the population of all employees of Treasury and Fund Mobilization Division Dr. Sardjito General Hospital, with 40 people who are participate as research samples. Data collection methods used questionnaires, while data analysis techniques used simple linear regression analysis analysis supported by F (F-test) and T (T-test) test and classical assumption test consisting of multicolinearity test, normality test and heteroscedasticity test. Based on the results of the analysis shows that job satisfaction has a positive and significant effect on the employee's performance on